2021
DOI: 10.30743/cheds.v4i2.3651
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Model Problem Based Learning (Pbl) Dengan Menggunakan Minp Maple Untuk Meningkatkan Hasil Belajar Pada Materi Termokimia

Abstract: Penelitian ini bertujuan untuk mengetahui pengaruh model problem based learning (PBL) menggunakan mind maple untuk mengningkatkan hasil belajar siswa pada materi termokimia. Metode penelitian adalah metode eksperimen semu (quasi eksperimen) yang populasinya seluruh siswa kelas XI-MIA di SMA Negeri 15 Medan. Sampel penelitian sebanyak 64 siswa yang ditentukan secara random sampling.  Sampel tersebut terdiri dari 2 kelas yaitu, kelas eksperimen (siswa yang dibelajarkan dengan mode PBL tanpa media dan kelas kontr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 2 publications
1
2
0
Order By: Relevance
“…<0.05), it can be concluded that the Problem Based Learning (PBL) learning model with the FILA chart design is assisted MindMaple have a significant effect on increasing students' metacognitive skills. This is in line with research Manurung & Pane (2020) there is a difference in the learning outcomes of the experimental class students who were taught the PBL model using the mind maple of 77.55 and the learning outcomes of the control class students who were taught the PBL model without the mind maple of 74.20.…”
Section: Scoresupporting
confidence: 89%
See 2 more Smart Citations
“…<0.05), it can be concluded that the Problem Based Learning (PBL) learning model with the FILA chart design is assisted MindMaple have a significant effect on increasing students' metacognitive skills. This is in line with research Manurung & Pane (2020) there is a difference in the learning outcomes of the experimental class students who were taught the PBL model using the mind maple of 77.55 and the learning outcomes of the control class students who were taught the PBL model without the mind maple of 74.20.…”
Section: Scoresupporting
confidence: 89%
“…MindMaple can be interpreted as a mind map template software to find out how activity planning can be carried out (Nafi'ah, et al, 2018). Mind maple can be used by teachers as a means of supporting learning that will be carried out during learning (Manurung & Pane, 2020). MindMaple in using the FILA chart, it has advantages, namely: 1) it looks familiar; 2) the Lite version of the MindMaple application does not cost anything (free) and has a size of 14.28 MB and can be used offline; 3) Has a variety of visualizations supporting concept maps; 4) There are facilities to add images, photos, videos, website links; 5) make it easier for students to make FILA charts directly without using stationery and save paper usage; 6) Different kinds of options are also available, such as resizing, changing color, adding shape.…”
Section: Scorementioning
confidence: 99%
See 1 more Smart Citation